Дослiдження розпаду 175Hf - Lashko, A. P.; Lashko, T. N.; Martinishin, V. A. (Publishing house "Academperiodika", 2019)
The intensities of lines of the internal conversion electron and y-rays emitted at the decay of 175Hf nucleus (T1/2 = 70 days) have been measured with the help of a п√2 magnetic B-spectrometer and two coaxial HPGe-detectors. On the basis of those data, the B-ray branching ratios and the log ft values for B-transitions are calculated. The limits on the log ft values for B-transitions to 175Lu levels 9/2+ at 113.8 keV, 9/2− at 396.3 keV, and 9/2+ at 546.6 keV have been found for the first time.